1980
DOI: 10.1128/jcm.12.2.288-290.1980
|View full text |Cite
|
Sign up to set email alerts
|

Production of phenylacetic acid by strains of Bacteroides asaccharolyticus and Bacteroides gingivalis (sp. nov.)

Abstract: Strains of Bacteroides asaccharolyticus and Bacteroides melaninogenicus subspecies isolated from human and animal sources were examined for the production of phenylacetic acid. B. asaccharolyticus strains isolated from oral sites in humans and monkeys always produced phenylacetic acid. B. asaccharolyticus strains isolated from human nonoral sites consistently failed to produce this product. This metabolic difference correlates with the genetic dichotomy recently found to exist between oral and nonoral B. asacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The physiological end products of the three asaccharolytic BPBs are shown in Table 1. While the three species produce 140 MAYRAND AND HOLT acetic, propionic, butyric, isobutyric, and isovaleric acids, only one species, B. gin giv'alis, produces phenylacetic acid (63,101,209). In addition, Bourgeau and Mayrand (9) found that the production of this acid was directly proportional to the Trypticase content of the medium and that L-phenylalanine, as well as peptides containing L-phenylalanine, also stimulated phenylacetic acid production.…”
Section: Nutrition Physiology and Cell Comiponentsmentioning
confidence: 98%
“…The physiological end products of the three asaccharolytic BPBs are shown in Table 1. While the three species produce 140 MAYRAND AND HOLT acetic, propionic, butyric, isobutyric, and isovaleric acids, only one species, B. gin giv'alis, produces phenylacetic acid (63,101,209). In addition, Bourgeau and Mayrand (9) found that the production of this acid was directly proportional to the Trypticase content of the medium and that L-phenylalanine, as well as peptides containing L-phenylalanine, also stimulated phenylacetic acid production.…”
Section: Nutrition Physiology and Cell Comiponentsmentioning
confidence: 98%
“…The species name Bacteroides gingivalis was proposed by Coykendall et al (2) to accommodate certain brown-toblack-pigmenting organisms, formerly identified as B. asaccharolyticus, found in association with periodontal disease that were probably B. gingivalis (5,7). Members of the species B. gingivalis have been implicated in various forms of periodontal disease and may be associated with other diseases in humans (9,17,23). Although B. asaccharolyticus and B. gingivalis are distinctly different in their DNA guanine-plus-cytosine content (moles percent, G+C) and DNA-DNA homology, their phenotypic characteristics are highly similar (9).…”
mentioning
confidence: 99%
“…Members of the species B. gingivalis have been implicated in various forms of periodontal disease and may be associated with other diseases in humans (9,17,23). Although B. asaccharolyticus and B. gingivalis are distinctly different in their DNA guanine-plus-cytosine content (moles percent, G+C) and DNA-DNA homology, their phenotypic characteristics are highly similar (9). Considerable effort has been exerted by various investigators to develop practical, reliable techniques that aid in differentiating or identifying B. gingivalis and B. asaccharolyticus and other phenotypically similar Bacteroides species.…”
mentioning
confidence: 99%
“…in the etiology and pathogenesis of human periodontal diseases and other oral and nonoral infections is being increasingly appreciated (15,17,22,23,26). Bergey's Manual of Systematic Bacteriology (6) recognizes nine black-pigmented Bacteroides species, distinguishable on the basis of phenotypic characteristics and DNA relatedness (1,3,5,7,8). A 10th species of black-pigmented Bacteroides, Bacteroides endodontalis, has recently been proposed (24).…”
mentioning
confidence: 99%